SISTEM PENGGAJIAN GURU DAN TENAGA KEPENDIDIKAN DI TK. ‘AISYIYAH BUSTANUL ATHFAL I KOTA PROBOLINGGO MENURUT PRINSIP-PRINSIP AKAD IJARAH - mohammad arifin; abdul wahab (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
During 2016 to 2019 there were many demonstrations carried out by educators and educational staff with a minimum guarantee of receiving monthly and no government allowance. This demonstration of educators is a silent proof of the inability of the government in the welfare of educators who need a non-PNS level, the complexity of being a PNS educator also cannot be solved by only teaching for more than 10 years. Anxiety like this certainly occurs in every region. To answer this we can answer through the payroll Sistem of educators and education personnel in kindergarten. ABA I Probolinggo City? and how is the implementation of the principles of the ijarah contract in kindergarten payroll systems. ABA I Kota Probolinggo according to the principles of the ijarah contract?To answer this question, this type of research is used (field field research) with a qualitative method. The data collection techniques used in this study include observation, interviews, and document study. The data that has been collected is then compiled and analyzed using descriptive methods, which describes the concept of implementing the payroll Sistem and the principles of the ijarah contract in kindergarten. ‘Aisyiyah Bustanul Athfal I Probolinggo City.The results of this study state that the implementation of the payroll Sistem and the implementation of the principles of the charity ijarah contract in the payroll Sistem in kindergarten. 'Aisyiyah Bustanul Athfal I City of Probolinggo is still general. Although in its application both parties have each benefited, this has not met the provisions of the ijarah agreement in accordance with sharia economic law.Keywords : Principles of Ijarah Agreement and Payroll Sistem